Polynomial epidemics and clustering in contact networks. - Szendroi, B; Csányi, G (2004)
It is widely known that the spread of the human immunodeficiency virus was slower than exponential in several populations, even at the very beginning of the epidemic. We show that this implies a significant reduction in the effective reproductive rate of the epidemic, and describe a general mechanism, related to the clustering properties of the disease transmission network, that is capable of explaining this reduction. Our considerations provide what is, to our knowledge, a new angle on polynomial epidemic processes, and may have implications for the choice of strategy against such epidemics.